Sustainable cargo check-in solutions for Tallink Silja Oyj - Valluru, Purnachand (2021)
The purpose of this thesis is to explore different methods that can be implemented by Tallink Silja for sustainable and efficient check-in of cargo trucks into their vessels operating in various Baltic cities. The topic explored is a real case scenario with on-ground implications. My thesis aims to deliver solutions by exploring different barriers that are products of the natural evolution of the human lifestyle and suggest solutions using technological advancements and innovations to overcome said barriers and increase efficiency. In order to understand this qualitative and multiple case study analysis based thesis more thoroughly. I took a look at different theoretical themes such as Sustainability in logistics, Rapid urbanisation and its effects, the need for Digitalisation and then move towards further explaining the current check-in methods and finally offer our researched and recommended solutions with giving a brief idea into the challenges that company might face implementing these solutions.